Stark control of electrons along nanojunctions - Liping Chen (Nature Portfolio, 2018)
Strong non-resonant few-cycle laser pulses can be used to induce ultrafast phase-controllable currents along nanojunctions but the microscopic origin is unclear. Here, the authors present time-dependent quantum transport simulations that recover the experimental observations and offer an intuitive picture of the effect.